Challenges faced in the implementation of localised advanced level geography syllabus: a case of Harare high schools - Marimo, Simon Tirivanhu (Midlands State University, 2015)
The paper examines the challenges met in implementing the Localized "A" Level Geography Syllabus. The study was conducted at 2006 in 52 Harare High Schools offering the localized "A" Level Geography syllabus. The sample for the study consisted of108 "A" Level Geography students, 54 "A" Level Geography teachers, 3 education officers and14 former Geography 'A ' Level students already enrolled at the University of Zimbabwe. The research used both qualitative and quantitative aspects of research. Data was analysed using the manual sort and count, grouping, coding, classifying and categorizing to identify trends and patterns as they were emerging. Thick description was also employed using information and excerpts from questionnaires, interviews, observations and document analysis. The major findings were that teachers are not using the new 'A" Level Geography syllabus in planning their lessons. Teachers are still using notes that they made from the previous syllabus and students' exercises, which are derived from the old syllabus. Teachers are not confident when teaching the new syllabus and in planning their lessons. The content in available textbooks is largely not relevant to the new "A" Level Geography syllabus as some case studies are out-dated and that the textbooks do not have local and regional examples. Teachers are having problems in implementing the new "A" Level syllabus as intended by the curriculum planners. The study recommends that teachers, as classroom practitioners, should discuss approaches in their districts or cluster workshops, seminars and staff developments on how to improve the implementation of this new "A" Level Geography syllabus with a view to making them feel more confident in the teaching and learning of Geography